Disability friendly : how to move from clueless to inclusive - Kemp, John D. (John Wiley & Sons, Inc., 2023)
"Although progress has been made around equality for marginalized groups defined by race, gender, sexual orientation and others - most organizations' Diversity, Equity and Inclusion (DEI) efforts do not include people with disabilities. Although 90% of organizations claim to prioritize diversity, only 4% consider disability in DE&I initiatives. Yet people with disabilities make up 15% of the population - about 1 billion people worldwide. They are all too often overlooked. Disability friendly starts with the roadblocks able people have to understanding and engaging people with disabilities, and how to get over the initial discomfort many able people have. It goes on to explain how businesses, schools, government, churches, and other organizations can open up to the contributions and talents of people with disabilities and create a culture of inclusion and reasonable accommodation. It explains the leader's role and how to communicate a vision for change that inspires others. Finally, it explains how to engage, recruit, and hire people with disabilities. This groundbreaking book will open the world's eyes to the overlooked potential of people with disabilities"--